Participatory Governance and Policy Diffusion in Local Governments in Korea: Implementation of Participatory Budgeting - Soonhee Kim (Korea Development Institute (KDI), 2016)
Government leaders' attention to participatory governance, public-private partnership, and community empowering has been increased in developing countries as well as developed countries as a way of enhancing public trust in government and overcoming economic and social challenges in governance. Korea is no exception. Especially, the evolution of participatory budgeting (PB) in the Republic of Korea shows very interesting dynamics in the context of democratization and decentralization. PB in Korea is a mandatory citizen participation program in local governments since enacting the Local Finance Act in 2011. The case of PB program in Korea presents an important policy diffusion process from a bottom-up approach to a top-down one concerning intergovernmental relations for implementing a citizen participation program. As PB has been implemented in all the local governments in Korea, it provides a great opportunity to conduct a nation-wide assessment study of the PB adoption and diffusion, local government capacity for the PB implementation, and the impacts of the PB on public administration and values in local governance. Focusing on local governments' experiences of PB implementation, "Participatory Governance and Policy Diffusion in Local Governments in Korea: Implementation of Participatory Budgeting," provides theoretical and practical insights for understanding policy diffusion, implementation capacity, impacts, and challenges. It further elaborates several policy recommendations for enhancing PB implementation capacity given the ongoing challenges of PB implementation, including weak financial independency of local governments, the relation between local government and local council, and the low level of citizen participation in the PB program.
Keywords: 330